Web solution to support real time systems - Pimentel, Diogo Santos (2015)
More and more every terminal behaves as a window to the web, being computers, smartphones, tablets, etc. With the advent of web technologies and its globalization, more and more service providers have to adapt to the new reality and follow the trend in order to not loose clients and even the quality of service. This evolution towards web applications has been increasingly observed in the tools used in day-to-day tasks. When leading companies in their market segment propose to make this technological evolution in its products and services, several factors must be studied and taken into account. In the case of solutions using real time communications integrated with its own hardware, several solutions propose to solve the problem, each with its pros and cons, but giving priority to the cutting-edge technologies, which, preferably are originally designed to answer the matters in the product context. Hence a priority to a study to answer the relevant matters for the product as well as the necessary tests to validate the proposed theory.